2010
DOI: 10.1259/bjr/19238690
|View full text |Cite
|
Sign up to set email alerts
|

Fractionated Helical Tomotherapy as an alternative to radiosurgery in patients unwilling to undergo additional radiosurgery for recurrent brain metastases

Abstract: ABSTRACT. Our clinic routinely treats brain metastases with stereotactic radiosurgery using a 6 megavoltage (MV) linear accelerator, cones, and a surgically attached head frame. Four patients declined repeat radiosurgery for new lesions due to their previous discomfort and a fifth patient could not complete radiosurgery because of uncontrolled nausea. Instead patients were treated with Helical Tomotherapy (HT). This report discusses the spatial dose distribution of HT as measured in a head phantom and the clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 16 publications
(18 reference statements)
0
5
0
2
Order By: Relevance
“…One comparative study found that the toxicity associated with HT was lower than that of 3D‐CRT. v Brain cancer: the results of 12 observational studies ( n = 290) showed that, the incidence of toxicities associated with HT for meningioma, intracranial tumors, and brain metastases was low, and there was no severe toxicity. The 1‐year survival rate reported in three of these studies was >80%; one study found that the 1‐year SR was 45% and the median SR was >1 year.…”
Section: Resultsmentioning
confidence: 99%
“…One comparative study found that the toxicity associated with HT was lower than that of 3D‐CRT. v Brain cancer: the results of 12 observational studies ( n = 290) showed that, the incidence of toxicities associated with HT for meningioma, intracranial tumors, and brain metastases was low, and there was no severe toxicity. The 1‐year survival rate reported in three of these studies was >80%; one study found that the 1‐year SR was 45% and the median SR was >1 year.…”
Section: Resultsmentioning
confidence: 99%
“…Less reported however is the use of HT for hypofractionated focal irradiation alone of lesions. Sanghera et al reported on five patients treated with HT who were unwilling or unable to undergo linac-based SRS and concluded that TomoTherapy represented a viable alternative ( 24 ). Tomita et al reported on 16 patients with 1–4 brain metastases treated focally to 35 or 37.5 Gy in 5 fractions of whom 2 developed a local recurrence at the treated site and 3 developed new intracranial metastases ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…HT is a unique IMRT delivery system capable of achieving highly conformal dose distributions with good coverage of intracranial targets and normal tissue sparing ( 19 ). Several reports have described the use of HT in the treatment of brain metastases both as an integrated boost within a simultaneous WBRT plan, and alone as a focal treatment ( 20 24 ). In addition, previous dosimetric investigations have indicated that HT possesses favorable dosimetric properties for the application of focal irradiation of metastatic lesions in comparison with more commonly used modalities including linac and Gamma Knife radiosurgical systems ( 25 27 ).…”
Section: Introductionmentioning
confidence: 99%
“…Cependant, l'objectif d'un geste chirurgical radical, tout en prenant le maximum de précaution pour des métastases parfois situées dans des zones cérébrales hautement fonctionnelles, nécessite une sélection de cas assez rigoureuse. La radiothérapie n'est pas en reste concernant les évolutions Correspondance : pierre-etienne.heudel@lyon.unicancer.fr technologiques, et il existe désor-mais différentes possibilités d'irradiation comme la tomothérapie hélicoïdale ou l'irradiation avec modulation d'intensité [18]. Malgré tout, pour les patientes qui présen-tent une atteinte métastatique céré-brale multiple ou une lésion unique inopérable, le traitement, le plus standard, demeure la radiothérapie sur l'ensemble de l'encéphale à la dose totale de 30 Gy en dix fractions.…”
Section: Introductionunclassified